The Performance of Hybrid Anaerobic Membrane Bioreactors (AnMBRs) Added with Powdered Activated Carbon (PAC) Based on Different Sludge Retention Times - Tan, E-Chuan; Tan, Sze Pin; Low, Meng Khai; Lo, Po Kim; Bashir, Mohammed J.K.; Liang, Andrew Chai Han; Nisar, Humaira; Ng, Choon Aun (Journal of Membrane and Separation Technology, 2015)
In this study, the effects of different sludge retention times (SRTs) on membrane fouling control with the addition of powdered activated carbon (PAC) were investigated for the anaerobic membrane bioreactors (AnMBRs). Chemical oxygen demand (COD), mixed liquor volatile suspended solids (MLVSS), food to microorganisms (F/M) ratio, particle size distribution, extracellular polymeric substances (EPS) and their relationships with membrane fouling were studied for AnMBR added with PAC at different SRTs. As SRT of the AnMBR increased to higher days, MLVSS concentration would increase and F/M ratio decreased and it was found to have a better membrane fouling control. It was also noticed that PAC addition would decrease EPS concentration and increased the floc size of the biomass which would help to reduce membrane fouling rate of AnMBRs.